2022
DOI: 10.3390/endocrines3020024
|View full text |Cite
|
Sign up to set email alerts
|

Familial Diabetes in Obese PCOS Predisposes Individuals to Compensatory Hyperinsulinemia and Insulin Resistance (IR) Also for Reduced Hepatic Insulin Extraction (HIE)

Abstract: Background: Polycystic ovary syndrome (PCOS) is a frequent reproductive disease characterized by hyperandrogenism, oligo /anovulation, and polycystic aspects at ultrasound. In these last years, a body of evidence disclosed the frequent occurrence in PCOS patients of insulin resistance (IR) and compensatory hyperinsulinemia. Aim: To evaluate whether any relationship exists between IR, compensatory hyperinsulinemia and familial predisposition to diabetes. Methods: A group of overweight/obese PCOS patients (n = 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…84 In addition, patients with PCOS with familial diabetes also showed ALT and AST plasma levels at the upper limit of normality and higher than in patients with PCOS without familial diabetes. 85 These data let us infer that a specific impairment might be induced by a familial predisposition to diabetes affecting hepatocyte functions. Indeed, patients with PCOS with familial diabetes showed a higher IR than patients with PCOS without familial diabetes when undergoing OGTT.…”
Section: Insulin Actions and Insulin Resistancementioning
confidence: 98%
See 4 more Smart Citations
“…84 In addition, patients with PCOS with familial diabetes also showed ALT and AST plasma levels at the upper limit of normality and higher than in patients with PCOS without familial diabetes. 85 These data let us infer that a specific impairment might be induced by a familial predisposition to diabetes affecting hepatocyte functions. Indeed, patients with PCOS with familial diabetes showed a higher IR than patients with PCOS without familial diabetes when undergoing OGTT.…”
Section: Insulin Actions and Insulin Resistancementioning
confidence: 98%
“…84 , 85 Recently, our group evaluated the hepatic insulin extraction (HIE) index in patients with PCOS who are overweight or obese and found that this index indicated impairment, specifically when familial diabetes was present in at least one first-degree relative (parents and/or grandparents). 84 , 85 …”
Section: Insulin Actions and Insulin Resistancementioning
confidence: 99%
See 3 more Smart Citations